Surgical site infections among patients underwent clen and clean-contaminated surgery in Hospital Universiti Sains Malaysia : risk factors, microbiological and staphylococcus aureus molecular profile - Jun Leong, Wong (2015)
Surgical site infections (SSI) are among the most commonly encountered healthcare associated infection. The incidence were closely been monitored as it is associated with considerable morbidity and mortality. The common aetiological agents responsible for the infection include Staphylococcus aureus, Streptococcus spp, Enterococcus spp, and Pseudomonas aeruginosa. The identification of the causative agents as well as their antimicrobial sensitivity pattern helps in the treatment plan. Therefore the aims of this study were to determine the incidence and risk factors of SSI as well as to identify the causative microorganisms and their sensitivity profile. This prospective cohort study was conducted from June 2013 until July 2014 at Hospital Universiti Sains Malaysia. Seventy-two patients underwent clean and clean-contaminated surgeries were consented preoperatively and strictly followed up for any signs of SSI for duration of 30 days post operation. Nasal screening for Staphylococcus aureus and Methicillin-resistance Staphylococcus aureus was carried out preoperatively. Tissue samples or wound swab from infected patients were taken for microbial identification and its sensitivity pattern. Staphylococcus aureus strain isolated were proceed to polymerase chain reaction analysis to detect the virulence genes (TSST, PVL, cna, hlg, icaA, and SdrE). The overall incidence rate of SSI was 18.1% specifically for clean and clean-contaminated surgeries are 20% and 11.8%, respectively. Significant risk associated with SSI by simple logistic regression analysis included patients admitted two days or more prior to surgery (OR 12.67; 95% CI, 2.02 to 79.53), underwent CABG surgery (OR 10.20; 95% CI, 2.66 to 39.08), underlying diseases (OR 9.46; 95% CI, 1.15 to 77.50), history of diabetes mellitus (DM) prior to the surgery (OR 9.40; 95% CI, 2.36 to 37.39), total hospitalization period more than seven days (OR 7.84; 95% CI, 2.12 to 29.0), duration of surgery more than four hours (OR 7.08; 95% CI, 1.84 to 27.27), and discharged home three days or longer after surgery (OR 5.13; 95% CI, 1.39 to 18.84). Multiple logistic regression method demonstrated that the patients who have history of DM (OR 6.97; 95% CI, 1.49 to 32.71) and underwent CABG surgery (OR 5.54; 95% CI, 1.22 to 25.03) had significant risks of SSI. Gram negative microorganism was the leading causative microorganism and in Staphylococcus aureus strains, icaA gene was the most common virulence gene detected. In conclusion, SSI among clean and clean-contaminated surgeries are high in our setting. DM and patients underwent CABG operation are at high risk to get SSI. Gram negative microorganisms are common as compare to Gram positive, however they are all sensitive strains.